Formation of Deontological Culture of Future Pharmacists in Higher Education Institutions of Ukraine - Konokh, A.; Naumchuk, V.; Konokh, A.; Shafranska, T. (My University, 2022)
One of the leading factors that enables the successful functioning of the pharmaceutical industry is staffing. Proper training of specialists, along with the formation of their professional characteristics, should also include the development of spirituality and morality. The purpose of this study is to substantiate and experimentally test the model of formation of deontological culture of future pharmacists in higher education institutions. The level of formation of deontological culture was determined by a set of methods using an integrative indicator. A total of 180 students and 26 teachers from medical colleges and 19 pharmacy staff took part in the study. At the formative stage of the pedagogical experiment, 61 applicants for higher education were involved. Our research has shown that deontological culture is associated with a system of values, professional and personal formations of the specialist, through which their moral consciousness is manifested in professional activities. The structure of the deontological culture of the pharmacist is determined by the humanistic worldview, empathy, communicative activity and personality qualities. The model of formation of deontological culture of future pharmacists includes a set of interconnected components that determine the semantic construction of this purposeful process, and its effectiveness is ensured by the implementation of organizational and methodological conditions such as organizational and pedagogical, specialized, mutually formative and cognitive and advanced. The results of the experimental test showed the effectiveness of the proposed model and the corresponding organizational and methodological conditions.
Keywords: Deontological Culture; Pharmaceutical Industry; Future Specialists; Institutions of Higher Education; Model